Causes of Blindness in Patients with Open Angle Glaucoma, an Alarming Situation - Muhammad Rafiq, Imran Ahmad, Bakht Samar Khan, Mubashir Rehman (Pakistan Journal of Ophthalmology, 2018)
Purpose: To determine the causes of blindness in patients with open angle glaucoma. Material and Methods: It was a retrospective cohort study in which 500 eyes with legal blindness were investigated. In all these patients detailed history was taken followed by examination including best corrected visual acuity, tonometry, gonioscopy and perimetry, central corneal thickness and where indicated other investigations like OCT, HRT and MRI were done. Results: The causes of blindness in patients with open angle glaucoma were late presentations (26%), misdiagnosis (13.60%), poor compliance (19.20%), unable to afford medications (8.4%), refusal of surgery (10.60%) and failure of medications (22.40%). Conclusion: Open angle glaucoma is a serious problem which can lead to blindness due to many reasons. Therefore patient must be well educated about the course and progression of disease.